HBR's 10 must reads on making smart decisions (Harvard Business Review Press, 2013)
Leading experts such as Ram Charan, Michael Mankins, and Thomas Davenport provide the insights and advice you need to: Make bold decisions that challenge the status quo. Support your decisions with diverse data. Evaluate risks and benefits with equal rigor. Check for faulty cause-and-effect reasoning. Test your decisions with experiments. Foster and address constructive criticism. Defeat indecisiveness with clear accountability